AICCRA Zambia – Affordability study with farmers using the CSA/CIS innovations report - Dahl, Hauke; Kakwasha, Keagan; Jacobs-Mata, Inga; Zulu, Sam; Hangombe, Botany; Musanshi, Wilbroad; Yobe Mumba, Kondwani Yobe (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The objective of the study was to understand end-users' capacity and willingness to purchase products and services scaled through the AICCRA Zambia CSA/CIS bundles. A total of 61 farmers were interviewed through in-person visits (3 for the Solar bundle, 15 for the Aquaculture bundle, 29 for the Seeds bundle, 14 for the Integrated Livestock/Legume bundle). Farmers were interviewed in Central Province (Chibombo, Kapiri Mposhi), Luapula Province (Mansa), and Eastern Province (Chipata, Chipangali, Nyimba). The key findings were as follows: 27% of the farmers were youths (below 35); 26% were females; 65% listed that they grow maize; 49% mentioned soya cultivation; 13% were involved in fish farming; 50% of farmers operated land equal to or below 2 hectares, and the average annual farming income is 29,800 Zambia Kwacha (1,397 USD). The study concluded that farmers are mostly resource-poor and have limited access to markets and financial services. Despite low affordability levels, the study indicates the positive impact of CSA advisory and climate information services.